Impact Of Implementation Of Decision Number: 150/Pid.B/2019/Pn.Lbo In The Case Of Employment Of Position - Riskawati Malapo (Universitas Negeri Gorontalo, 2019)
Embezzlement is one of the criminal acts that can harm many people, especially if it is done by taking advantage of positions as regulated in Articles 372-376 of the Criminal Code. One of them in the decision 150/pid.b/2019/pn.lbo seen legal norms that were ignored by the judge, namely the norms of certainty, justice and benefit. pid.b/2019/pn.lbo and to find out the impact of the application of sanctions on the decision number: 150/pid.b/2019/pn.lbo. The research method used is normative legal research with a statutory approach. The results of the research show that the punishment in Decision Number: 150/pid.b/2019/pn.lbo has not fulfilled justice and legal certainty because the sentence imposed by the judge is only 10 months in prison. Meanwhile, legal benefits have been achieved because of the punishment imposed because later the cooperative and the victim will feel more calm and secure in conducting transactions at the Karya Cipta Savings and Loans cooperative. Furthermore, the juridical implications that arise are the non-fulfillment of the mandate of Article 374 of the Criminal Code regarding embezzlement with weights. The fact is that the defendant structurally has a position in the Karya Savings and Loans Cooperative which makes the sentence more severe.Keywords: Criminal Code, Embezzlement, Decision Number : 150/pid.b/2019/pn.lbo